THE ROLE OF SELF-CONFIDENCE IN MEDIATING THE EFFECTS OF SKILL PRACTICES AND TRAINING ON EMPLOYEES' PERFORMANCE - Sutarto, Sutarto; Setyaningrum, Retno Purwani; Rezeki, Fitri (Jurnal Aplikasi Manajemen, 2022)
This study examines the direct effect of skill practices and training on employees' performance and the indirect effect of skill practices and training on employees' performance through self-confidence. This study was conducted at PT. Mulia Glass Float Division, Cikarang, Bekasi, West Java. This study is a quantitative study that collected data using a survey technique through a questionnaire. The data was then processed using PLS 3.3.3 software. The study population was 151 employees. Based on purposive sampling, the entire population was used as a sample. The results showed that self-confidence had a positive effect on employees' performance, skill practices had a positive impact on self-confidence, skill practices had a positive effect on employees' performance, training had a positive impact on self-confidence, and training had no effect on employees' performance, skill practices had a positive effect on employees' performance through self-confidence mediation, and training had a positive effect on employees' performance through self-confidence mediation. The expertise possessed by employees and the training provided could increase the employees' confidence that they could conduct their duties and responsibilities properly. Consecutively, it affected increasing employees' performance. This study is expected to be a reference for company management to conduct training to improve employees' skill practices continuously. It is also expected to increase employees' self-confidence and have an impact on improving employees' performance.